Multifunctional Nanomaterials: Synthesis, Properties, and Applications 2.0 - Yadav, Raghvendra Singh (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint consists of scientific papers that had been published and covered the synthesis, characteristics, and applications of multifunctional nanomaterials. Smart nanoparticles with two or more engineered properties or characteristics make up multifunctional nanomaterials. These versatile nanomaterials have impressive structural and physical characteristics, which has expanded their industrial application. This reprint will be useful to academics, scientists, engineers, students, and industrial researchers.